The processual life of neoliberalisation: permutations of value systems and normative commitments in a co-operative trust setting. Issue 11 (2nd November 2019) - Wilkins, Andrew
ABSTRACT: Since 2010 the government in England has committed to accelerating the expansion of academies ('state-funded independent schools') through displacing the role of local government as principal manager and overseer of schools. In response increasing numbers of schools are embracing the co-operative trust model to improve economies of scale, facilitate stakeholding and community resilience and resist capture from the monopolising tendencies of some large multi-academy trusts seeking wholesale takeover of certain underperforming schools. Yet there are concerns that co-operative schools do not represent a radical departure from routines of neoliberalism – defined by managerial deference, technocratic efficiency, upward accountability and performativity – despite clear signs that co-operative schools promote themselves as jointly-owned, democratically-controlled enterprises. In this paper, I adopt a 'processual view of neoliberalisation' [Peck, J., and A. Tickell. 2002. "Neoliberalizing Space." Antipode 34 (3): 380–404] to complicate the idea that co-operative schools can be judged in binary terms of 'either/or' – neoliberal or democratic, exclusionary or participatory – and instead point to the variegated organisational life of co-operative schools and their messy actualities as they straddle competing and sometimes conflicting sets of interests, motives and demands in their practice of school governance.